Influence of emotional intelligence on the academic performance of students at a national university in Perú - Barra-Quispe, David Eleazar; Mamani-Flores, Adderly; Atencio-Mendoza, Claudia María Ricardina; Ferro-Supo, Francis Walter; Chura-Flores, Juan Carlos; Huanacuni-Zapana, Tony Henry; Huanca-Quispe, Samuel; Florez-Florez, Osmar Jose (Edelweiss Applied Science and Technology, 2024)
Emotions can be both a help and a hindrance when studying, it is easy to fall into the mistake that there are "good" emotions and "bad" emotions. However, optimism could turn into self-esteem, when we think that we already know everything and will do very well, and we "let go of the reins" much sooner than necessary. To do this, the emotional state and its possible interference in academic performance must be studied. The objective was to assess the correlation of the level of emotional intelligence and the academic performance of the students of the Professional School of Anthropology of the UNA - Puno. It is at the relational level of inquiry; it is quantitative, analytical, observational, prospective and cross-sectional. We worked with 256 university students from I to VIII semester 2020-II, a virtual self-assessment questionnaire of Emily Sterrett's emotional intelligence was used, and the final average of the semester was collected. As a result, through the Chi-square statistical test, the statistical correspondence of 4 areas of emotional intelligence (emotional self-awareness, emotional self-confidence, self-control capacity and social competence) with academic performance was evidenced.